Radiographic pathology for technologists - Kowalczyk, Nina; Kowalczyk, Nina; Mace, James D. (Mosby/Elsevier, 2009)
Presents information on pathologic processes you need on a daily basis, with coverage of 150 of the most commonly diagnosed injuries and abnormalities. Each chapter of this book begins with an explanation of anatomy and physiology.